Clinical Outcome of Paraclinoid Internal Carotid Artery Aneurysms After Microsurgical Neck Clipping in Comparison with Endovascular Embolization - Bae, Dong-Hyun; Kim, Jae-Min; Won, Yu-Deok; Choi, Kyu-Sun; Cheong, Jin-Hwan; Yi, Hyeong-Joong; Kim, Choong-Hyun (Journal of cerebrovascular and endovascular neurosurgery, 2014)
Because of the complex anatomical association among vascular, dural, and bony structures, paraclinoid internal carotid artery (ICA) aneurysms remain a major challenge for vascular neurosurgeons. We studied the clinical outcomes of 61 paraclinoid ICA aneurysms after microsurgical clipping in comparison with endovascular coiling. Between January 2008 and December 2012, we treated 61 paraclinoid ICA aneurysms created by surgical clipping or endovascular coiling. Preoperative neurologic status and postoperative outcome were evaluated using the Glasgow coma scale (GCS) and the modified Rankin scale (mRS). Postoperative hydrocephalus and vasospasm were reviewed using the patients' medical charts. Most patients were in good clinical condition before the operations and had good treatment outcomes. Clinical vasospasm was observed after the operation in five patients, and hydrocephalus occurred in six patients. No statistically significant difference regarding aneurysm size, sex, GCS score, H-H grade, and mRS was observed between the surgical clipping group and the endovascular coiling group. In addition, the treatment results and complications did not show statistically significant difference in either group. Surgical occlusion of paraclinoid ICA aneurysms is difficult; however, no significant differences were observed in the treatment results or complications when compared with coil embolization. In particular, use of an adequate surgical technique may lead to better outcomes than those for coil embolization in the treatment of large and/or wide-neck paraclinoid ICA aneurysms.